Ekspektasi Pendapatan, Penggunaan Media Sosial, E-Commerce dan Minat Berwirausaha di Masa Pandemi Covid-19 - Mahadewi, Gusti Ayu Putu Agung; Sari Widhiyani, Ni Luh (E-Jurnal Akuntansi; Vol 33 No 6 (2023)DO - 10.24843/EJA.2023.v33.i06.p014, 2023)
The study aims to analyze the effect of income expectations, use of social media and e-commerce on the interest in entrepreneurship for students of the accounting undergraduate study program, Faculty of Economics and Business, Udayana University. The analysis technique used is multiple linear regression analysis with the method of determining the sample, namely purposive sampling. The sample used was 151 respondents. Data collection was carried out by distributing questionnaires. The results showed that income expectations, use of social media and e-commerce had a significant positive effect on the interest in entrepreneurship of students of the undergraduate accounting study program, Faculty of Economics and Business, Udayana University. Keywords: Income Expectations; Social Media; E-Commerce; Entrepreneurial Interest.